e-Weight train / Mohd Afif Mohd Yatid - Mohd Afif , Mohd Yatid (2006)
This project documentation describes in detail the information regarding the project e-Weight train. The first part of this thesis is primarily divided into four chapters that is Introduction, Literature Review, Methodology and System Analysis and Requirement. The second part consist of three chapters; System Design, System Testing and System Evaluation. Chapter I introduction will give the reader an overview of what this thesis is all about. Also, the objectives for developing this project the targeted user group project limitations the scope coverd by this project and an estimated schedule to finish the proejct are clearly stated. In chapter II, Literature Review a thorough review on smiliar existing systems is carried out in order to obtain a better understanding with regards to the proposed project. It provides developers with some knowledge and insights into the strenghts and limitations of several development tools that is available in the market. The software and scripting languages best used to develop the project is also researched. In chapter III methodology will be discussed the right type of methodology used for completing every activity in the System Development Life Cycle and also tools to be used for the project. In chapter IV, system analysis and requirement this is where the system requirement, system interface and reporting requirement, nonfunctional requirement and software analysis is discussed. In chapter V, System Design, the development of the proposed project will be discussed and ascertained. This includes system functionality design and module functionality design. It shows the modules involved in the system and the data flow when information is passed. In chapter VI, System Testing is broken down into three distinctive phase; unit testing, integration testing and system testing. Some of the methods such as function testing, performance testing, acceptance testing and installation testing were used to facilitate this operation. Finally, in chapter VII System Evaluation the difficulties and problems encountered during the solutions to the problems, the strengths and the limitations of the system being developed and the future enhancement of the system are throughly discussed.